Public Transportation Selection Application Based On Decision Support System - Ying, Lee Suet; Mei, Lee Jun; Shi, Lim Mei; Hui, Kee Hong; Arbaiy, Nureize Binti (International Journal of Advanced Science Computing and Engineering, 2020)
In Kuala Lumpur, there are various types of public transport such as bus and multiple types of rail transport. This facilitates the residents in Kuala Lumpur in terms of mobility and can reduce the level of traffic congestion around Kuala Lumpur. However, some people might get confused about the alternative routes when they are using the public transport. Next, road user might find information from maps and Internet which requires them to analyse and decide the routes by themselves. In addition, complex scheduling and routes of public transportation are hard to understand for the public. Besides, road users are not aware of better route and public transport available based on their requirement. In the end, they might be getting jam-packed on the road due to the limited information on the current available public transportation. Therefore, a decision support system is proposed to generate a type of public transport which suits with the criteria selected by the user. The system consists of five main modules and involves common users and system administrators. The application is written in Java programming language. Android Studio is used as software development and MySQL database. It is expected that this application will be able to help users to get public transportation options that suit the criteria they need.